Neutrophilic Cell-Free Exudate Induces Antinociception Mediate by the Protein S100A9 - Rosana L. Pagano; Mario Mariano; Renata Giorgi (Hindawi Limited, 2006)
Calcium-binding protein S100A9 (MRP-14) induces antinociceptive effect in an experimental model of painful sensibility and participates of antinociception observed during neutrophilic peritonitis induced by glycogen or carrageenan in mice. In this study, the direct antinociceptive role of the protein S100A9 in neutrophilic cell-free exudates obtained of mice injected with glycogen was investigated. Mice were intraperitoneally injected with a glycogen solution, and after 4, 8, 24, and 48 hours, either the pattern of cell migration of the peritoneal exudate or the nociceptive response of animals was evaluated. The glycogen-induced neutrophilic peritonitis evoked antinociception 4 and 8 hours after inoculation of the irritant. Peritoneal cell-free exudates, collected in different times after the irritant injection, were transferred to naive animals which were submitted to the nociceptive test. The transference of exudates also induced antinociceptive effect, and neutralization of S100A9 activity by anti-S100A9 monoclonal antibody totally reverted this response. This effect was not observed when experiments were made 24 or 48 hours after glycogen injection. These results clearly indicate that S100A9 is secreted during glycogen-induced neutrophilic peritonitis, and that this protein is responsible by antinociception observed in the initial phase of inflammatory reaction. Thus, these data reinforce the hypothesis that the calcium-binding protein S100A9 participates of the endogenous control of inflammatory pain.